Study on optimization measures for water level fluctuation of large water conveyance aqueducts. - Jian Chen; Yangyang Tian; Huijie Zhang; Hongling Shi (PLoS ONE)
This paper addresses the issue of water surface fluctuations in aqueducts caused by the Karman Vortex Street phenomenon, which significantly impacts the structural stability and water delivery efficiency of the aqueducts. Based upon existing research findings, a representative three-dimensional fluid dynamics model is developed to optimize the transition section and tail pier structure of the aqueduct, with the objective of reducing water level fluctuations and improving hydraulic stability.The research focuses on improving the symmetry of both the transition section and the tail pier, optimizing the tail pier structure, and analyzing its wave attenuation effect. The experimental results demonstrate that a conical tail pier performs better than a platform-shaped tail pier in eliminating water surface fluctuations, significantly reducing turbulent energy dissipation at the exit transition section, maintaining a relatively stable Froude number, and achieving a stable flow pattern. Furthermore, by comparing the total head loss at the outlet tapering section, it is found that a shorter (e.g.,15-meter) conical tail pier results in lower head loss than a longer (e.g.,35-meter) conical tail pier, indicating that a compact conical tail pier is more effective. This suggests that shorter tail piers are generally more effective in reducing head loss and improving flow stability. These findings offer valuable insights for optimizing tail pier selection in aqueduct design.This study highlights the crucial role of tail pier structure in reducing water surface fluctuations caused by the Karman Vortex Street phenomenon, thereby providing theoretical support and practical guidance for improving the structural stability and water delivery efficiency of aqueducts.